Rural-Urban Migration, Childbearing Decision-Making, Fertility and Contraceptive Perspectives of Street Adolescents and Youth in Kampala, Uganda - Bwambale, Mulekya Francis; Moyer, Cheryl A.; Bukuluki, Paul; van den Borne, Bart (Frontiers in Reproductive Health, 2022)
Introduction This paper aims to describe and assess social demographic factors associated with childbearing decision-making, fertility and contraceptive intentions among street adolescents and youth in Kampala, Uganda while considering rural-urban migration as an explanatory factor. Materials and Methods A cross-sectional survey of 513 adolescents and youth aged 12–24 years self-identifying as street adolescents and youth were interviewed with a structured questionnaire in 2019. Street adolescents and youth who migrated from other rural districts to Kampala were compared with those from the city. Logistic regression was performed to assess associations between the independent factors and personal childbearing decision-making, fertility and contraceptive intentions. Results Overall, 80.31% of the street adolescents and youth had a rural-urban migration experience. Fifty six percent (56.32%) of the street adolescents and youth made personal childbearing decisions, 94.15% expressed intentions to have children in the future and 42.88% expressed intentions to use contraceptives in the future. Intentions to use contraceptives were significantly higher among males (58.75%) than females (20.00%), and higher among migrants (65.91%) compared to non-migrants (34.09%). Contraceptive intentions were positively associated with self-perceived permanent residential status (aOR = 10.26, 2.70–39.08), intra-urban mobility (aOR = 4.99, 95%CI 1.50–6.59) and intentions to migrate to other towns within the country (aOR = 5.33, 95%CI 1.59–17.80). Being married (aOR = 0.13, 95%CI 0.02–0.85), a large shelter population size (aOR = 0.13, 95%CI 0.03–0.63) and having repeat migrations between the city and home district (aOR = 0.23, 95%CI 0.05–0.94), including migration-associated challenges reduced the odds of street youth's personal childbearing decision-making, while belonging to a social support group increased the odds of childbearing decision-making. We found no significant association between social demographic characteristics and fertility intentions. Discussion Factors that influenced personal childbearing decision-making and contraceptive intentions among street adolescents and youth in Kampala operate mainly at the interpersonal and community levels, with marital status, shelter population size, rural-urban migration and its associated challenges associated with childbearing decision-making. Interventions to promote childbearing decision-making and contraceptive use among street adolescents and youth should take into consideration their migration and intra-urban mobility patterns.